Pore and mineral structure of rock using nano-tomographic imaging. Issue 1744 (2015) - Kuva, Jukka; Voutilainen, Mikko; Lindberg, Antero; Parkkonen, Joni; Siitari-Kauppi, Marja; Timonen, Jussi
ABSTRACT: In order to better understand the micrometer-scale structure of rock and its transport properties which arise from it, seven monomineral samples from two sites (Olkiluoto and Sievi, Finland) were studied with micro- and nanotomography and scanning electron microscopy. From the veined gneiss of Olkiluoto we studied biotite, potassium feldspar, plagioclase (composition of oligoclase) and cordierite, and from Sievi tonalite biotite and two grains of plagioclase (albite). These minerals were the main minerals of these samples. Samples were carefully separated and selected using heavy liquid separation and stereomicroscopy, their three dimensional structure was imaged using X-ray tomography, and their precise mineral composition was determined using scanning electron microscopy and energy-dispersive X-ray spectroscopy (SEM/EDS). The micrometer-scale mineral structure of these samples was observed together with their pores and fissures, and alteration effects were identified whenever applicable. Nanotomography combined with SEM analysis was concluded to be a good tool for analyzing effects of alteration in monomineral samples.